Continuous rapid dechlorination of p-chlorophenol by Fe-Pd nanoparticles promoted by procyanidin. (29th June 2019) - Liu, Mingyue; Huang, Renliang; Li, Chuanxi; Che, Mingda; Su, Rongxin; Li, Shuzhou; Yu, Jing; Qi, Wei; He, Zhimin
Graphical abstract: Highlights: Procyanidin as a stabilizer to manipulate the size distribution of Fe nanoparticles. Procyanidin as a scavenger to prevent the precipitation of the generated Fe ions. High dechlorination performance towards p -chlorophenol over a wide pH range. Procyanidin enhanced dechlorination efficiency of Fe-Pd NPs by 2 magnitudes. The generated Fe ions were mainly present as bis- and tris-PROC-Fe complexes. Abstract: Nanoscale zero-valent iron has been widely applied in environmental remediation and toxic waste treatment, especially for the degradation of persistent organic pollutants (POPs). However, the dechlorination activity of Fe nanoparticles (Fe NPs) can be suppressed by the precipitation of iron oxides generated from the corrosion of Fe-Pd NPs under alkaline conditions, leading to a decreased dechlorination efficiency. Faced with this challenge, we report a highly effective dechlorination system that functions over a broad pH range and especially well under alkaline conditions in this work. Procyanidin (PROC), a natural polyphenol, was utilized as a stabilizer to manipulate the size distribution of Fe-Pd NPs and, more importantly, as a scavenger of Fe ions to prevent iron oxide precipitation. Experiments and theoretical calculations reveal that the generated Fe ions was mainly present in the form of bis- and tris-PROC-Fe complexes in the reaction solution. Compared with pristine Fe-Pd NPs, the PROC-modified Fe-Pd NPs had a dechlorination efficiency that was increased 20-fold (pH 9.0). Notably, a normalized rate constant was enhanced by more than 2 orders of magnitude compared to the previously reported dechlorination systems. The PROC-modified Fe-Pd NPs showed excellent dechlorination efficiency over a wide pH range (2.3–13.0).